Potential of fenugreek seed extract for health, the environment and the economy - Hamid Nour, Abdurahman; Akbari, Sweeta; Rosli, Mohd Yunus; Mona, Timan (2021)
Bioactive compounds extracted from natural sources and plants have received potential interest in food, cosmetic and pharmaceutical industries. Recently, the use of synthetic antioxidants such as BHT and BHA are not very encouraged to be used in food, pharmaceutical and cosmetic products. Beside the application of synthetic surfactants at high volume in health-related products are prohibited by world health organization (WHO) due to their risks and side effects. In this research, fenugreek seed has been used to produce a multifunctional bioactive extract containing saponin, phenolic and antioxidant compounds via microwave-assisted extraction technology. Fenugreek seed is a low price and abundantly found material with many health benefits. The extract characterized using LC-QTOF-MS, FTIR, SEM, and also determined the total saponin, total phenolic compounds inside the extract. Due to the high amount of saponin inside the extract, it has been tested for emulsification and wettability properties. In addition, the properties of saponin makes it a good biosurfactant for food, cosmetic, pharmaceutical, water and soil treatment industries. It has been reported that biosurfactant are efficiently used for removal of heavy metals from water and soil.